3 Archives of Maryland 255 - (:unkn) unknown (My University, 1648)
licenses previously issued for "killing of Wild Hoggs [e]mploying Indians to kill deere with Gunnes" both to residents and non-residents of Maryland "hath occasioned some inconvenience & hath given great offence to divers of the Inhabitants of this Province," all existing licenses were repealed
Keywords: HUNTING REGULATION